Hydrothermal Synthesis, Crystal Structure, and Magnetism of Na2[Ir(OH)6] and its Dehydration to Na2IrO3 - Albrecht, Ralf; Poddig, Hagen; Hunger, Jens; Ruck, Michael; Benrath, Philipp; Moeller, Angela; Doert, Thomas (Zeitschrift für Anorganische und Allgemeine Chemie, 2021)
Yellow single-crystals of Na2[Ir(OH)6] were obtained by hydrothermal synthesis in 20 m sodium hydroxide solution at 473 K within 5 hours. X-ray diffraction on a single-crystal revealed the trigonal space group (Formula presented.) (no. 148) with lattice parameters a=582.76(3) pm and c=1399.30(8) pm at 100(1) K. Na2[Ir(OH)6] crystallizes in a hettotype of Mg(OH)2 (brucite) and is isostructural to Na2[Sn(OH)6]. The oxygen atoms are arranged in a hexagonal close packing, Na+ and Ir4+ ions occupy the octahedral voids in every second layer in an ordered manner, the voids of the next layers remain empty. The hydroxidometalate layer can be seen as isolated [Ir(OH)6]2− octahedra, which are embedded in a honeycomb net of alkali metal cations. Temperature-dependent magnetic measurements revealed paramagnetic behavior with an effective moment of 1.9 μB per iridium ion. The thermal decomposition of Na2[Ir(OH)6] in air starts at about 220 °C and results in pure Na2IrO3.
CRIS-Team Scopus Importer:2022-04-14
Keywords: crystal structure; hydrothermal synthesis; hydroxidoiridates; magnetization; thermal analysis